PENERAPAN MODEL PEMBELAJARAN LANGSUNG DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA SEKOLAH DASAR - Luthfianti (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study discusses the application of the direct instruction model in improving elementary school students’ understanding of mathematical concepts. The background of this study is based on the importance of developing students’ conceptual understanding in mathematics, especially at the elementary level, where learners still require structured and concrete learning processes. The purpose of this study is to describe the concept, steps, roles of teachers and students, as well as the advantages and disadvantages of the direct instruction model in mathematics learning. The method used in this study is a literature review, which relies on relevant educational books as the main source of data. The findings show that the direct instruction model can help students understand mathematical concepts more systematically through clear explanations, guided practice, and independent exercises. However, this model also has limitations, particularly in reducing students’ active participation if not combined with other learning strategies. Overall, the direct instruction model is effective in improving students’ basic understanding of mathematics when applied appropriately and balanced with other methods.